A method for preparing MQ resin with low pentamer content

By adopting continuous preparation method and low-temperature strong acid treatment technology during the preparation process of MQ resin, the problem of high pentamer content is solved, and the application performance and tackification effect of MQ resin are improved.

CN116333316BActive Publication Date: 2025-02-18WANHUA CHEM GRP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211624719.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-16
Publication Date
2025-02-18
Estimated Expiration
2042-12-16

AI Technical Summary

Technical Problem

During the preparation of MQ resin, the pentamer produced has a low boiling point and is prone to evaporate during high-temperature curing, which affects its application in pressure-sensitive adhesives and other fields. The prior art has failed to effectively control or reduce the content of pentamers.

Method used

Using a continuous preparation method, aged in the polycondensation reactor to obtain Q prepolymer, and adding strong acid to the organic phase at low temperature for secondary treatment, interrupting Si-O between M units and Q units in the pentamer The bond promotes the polycondensation reaction of Q units and reduces the content of pentamers.

Benefits of technology

It effectively reduces the content of pentamer in MQ resin, improves its initial viscosity and viscosity-enhancing effect in pressure-sensitive adhesive applications, and reduces the amount of MQ resin added in the formula.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004003681520000011
    Figure HDA0004003681520000011
  • Figure HDA0004003681520000012
    Figure HDA0004003681520000012
  • Figure HDA0004003681520000021
    Figure HDA0004003681520000021
Patent Text Reader

Abstract

The present invention provides a method for preparing a MQ resin with a low pentamer content, the method comprising the following steps: S1: adding water glass and hydrochloric acid to a polycondensation reactor, and fully mixing, and then aging to obtain a Q prepolymer; S2: adding a capping agent, an alcohol reagent and a solvent to the Q prepolymer for a capping reaction; S3: static phase separation to obtain an organic phase containing the MQ resin, adding a strong acid to the organic phase, and mixing at a temperature below 50°C; S4: washing with water to remove the strong acid in the organic phase obtained in step S3, and performing rectification and separation to obtain a MQ resin with a low pentamer content. The method according to the present invention can effectively reduce the content of pentamers in the MQ resin, improve the application performance of the MQ resin, enhance its initial adhesion in the application of pressure-sensitive adhesives and the viscosity-increasing effect of low-viscosity adhesives, and can effectively reduce the amount of MQ resin added in the formula.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of MQ resin synthesis, and in particular relates to a method for continuously preparing MQ resin with low pentamer (tetrakis(trimethylsiloxy)silane) content. Background Art

[0002] Silicone resin products have excellent thermal stability, electrical insulation, weather resistance, and biocompatibility. They are widely used in defense and military industry, electrical industry, light industrial products, rubber and plastics, food hygiene and other industries, playing an irreplaceable role in the field of materials. MQ resin is a type of silicone resin, which consists of a single functional group (M group) chain link R3SiO 1 / 2 and tetrafunctional (Q group) chain SiO 4 / 2 It is generally believed that the MQ resin has a double-layer three-dimensional structure with a dense spherical body. The core part is connected by Si-O chains, which is a cage-like SiO2 with a higher density; the shell part is connected by R3SiO 1 / 2 MQ resin has good adhesion, heat resistance, weather resistance, flexibility and many other properties, and has great application value in industry. Its main application areas include pressure-sensitive adhesives and liquid silicone rubber. However, during the preparation of MQ resin, a low molecular weight pentamer containing only one Q unit and four M units is generated: tetrakis(trimethylsiloxy)silane, whose structure is shown in the attached figure. Figure 1 When MQ resin is used in pressure-sensitive adhesives and other fields, the pentamer has a low boiling point (103-106℃ / 2 mmHg(lit.)) and is easily volatilized from the main body of the product after high-temperature curing. Therefore, the content of pentamer will directly affect the application of MQ resin in pressure-sensitive adhesives and other fields. At present, there is no specific patent that mentions how to control and reduce the content of pentamer in the preparation process of MQ resin.

[0003] CN109438709A provides a method for preparing methyl MQ resin, wherein acid, sodium silicate solution, organic solvent, trimethylchlorosilane and a mixture of high-purity hydrocarbon solvent are sequentially added to a three-necked flask under stirring, and then refluxed for reaction, and high-purity hydrocarbon solvent is added again, stirred, allowed to stand, and layered; the organic layer is washed with water 2-3 times to obtain methyl MQ resin. The invention uses high-purity hydrocarbon solvent to replace toluene to obtain methyl MQ resin with narrow molecular weight distribution, and by changing the reaction temperature, reaction time and concentration of hydrochloric acid of sodium silicate aqueous solution and acid, methyl MQ resin with a molecular weight greater than 10000 g / mol is obtained.

[0004] CN109553773A discloses a method for preparing methyl MQ resin, which comprises dripping an organic solvent into a sodium silicate aqueous solution, stirring and standing the solution, generating a precipitate at the bottom of the sodium silicate aqueous solution, taking out the sodium silicate aqueous solution, and then adding corresponding water to obtain a refined sodium silicate aqueous solution. Acid and the refined sodium silicate aqueous solution are reacted, an organic solvent and a silyl ether are added, and the reaction is refluxed, and the reaction product is separated, purified, and dried to obtain a methyl MQ resin. In the invention, the methyl MQ resin prepared after refining the sodium silicate aqueous solution has a higher molecular weight than the unrefined one, and a relatively narrow molecular weight distribution.

[0005] The above prior arts all provide methods for preparing narrow molecular weight MQ resins and increase the molecular weight of MQ resins by certain methods, but do not specifically propose a solution for reducing the pentamer content in MQ resins, and all of them are intermittent processes. Therefore, there is still a need for a continuous preparation method for MQ resins with low pentamer content to improve the performance of MQ resins in applications. Summary of the invention

[0006] The pentamer generated in the preparation of MQ resin has a low boiling point. When used in the fields of pressure-sensitive adhesives, it is easy to volatilize from the main body of the product during high-temperature curing. The content of pentamer in the MQ resin product will directly affect the application in the fields of pressure-sensitive adhesives. The current prior art has not yet involved how to control and reduce the content of pentamer in the preparation process of MQ resin. The purpose of the present invention is to provide a continuous preparation method for MQ resin with low pentamer content, which can effectively reduce the content of pentamer in the synthesis of MQ resin, improve its initial adhesion in pressure-sensitive adhesive applications and the viscosity-increasing effect of low-viscosity adhesives.

[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0008] According to a first aspect of the present invention, there is provided a method for preparing a MQ resin having a low pentamer content, the method comprising the following steps:

[0009] S1: adding water glass and hydrochloric acid into a polycondensation reactor, mixing them thoroughly, and then aging to obtain a Q prepolymer;

[0010] S2: adding a capping agent, an alcohol reagent and a solvent to the Q prepolymer to perform a capping reaction;

[0011] S3: static phase separation to obtain an organic phase containing MQ resin, adding a strong acid to the organic phase, and mixing at a temperature below 50°C;

[0012] S4: washing with water to remove the strong acid in the organic phase obtained in step S3, and performing distillation separation to obtain MQ resin with low pentamer content.

[0013] Preferably, the preparation method is a continuous process, and the polycondensation reactor is a tubular reactor or a kettle reactor.

[0014] Preferably, in step S1, the concentration of water glass is 16-25 wt %, preferably, the concentration of water glass is 20 wt %.

[0015] Preferably, in step S1, the amount of hydrochloric acid added should make the pH of the reaction system less than 1.

[0016] Preferably, in step S1, the aging time is 1 to 10 minutes.

[0017] Preferably, in step S2, the end-capping agent is one or more selected from trimethylchlorosilane, hexamethyldisiloxane, tetramethyldivinyldisiloxane, and dimethylvinylchlorosilane.

[0018] Preferably, the amount of the end-capping agent added is 20-40 wt %, based on the weight of the added water glass.

[0019] Preferably, in step S2, the alcohol reagent is one or more selected from methanol, ethanol, isopropanol and butanol, preferably isopropanol.

[0020] Preferably, the alcohol reagent is added in an amount of 20 to 40 wt % based on the weight of the added water glass.

[0021] Preferably, in step S2, the solvent is one or more selected from toluene, xylene, hexamethyldisiloxane and long-chain hydrocarbon solvents.

[0022] Preferably, the added amount of the solvent is 30 to 100 wt %, based on the weight of the added water glass.

[0023] Preferably, the long-chain hydrocarbon reagent is a saturated alkane having 6 to 20 carbon atoms.

[0024] Preferably, in step S2, the reaction temperature of the end-capping reaction is 60-90°C.

[0025] Preferably, in step S3, the strong acid is one or more selected from concentrated sulfuric acid, trifluoromethanesulfonic acid, benzenesulfonic acid, and trimethylsulfonic acid.

[0026] Preferably, the amount of the strong acid is 0.1-0.5 wt %, based on the weight of the added water glass.

[0027] Preferably, in step S3, mixing is performed at a temperature of 20 to 40°C.

[0028] In the present invention, the organic phase after phase separation in step S3 is a crude product of MQ resin, and the content of pentamers in the resin that have not been treated with low-temperature strong acid for secondary treatment is usually between 1% and 3%. Strong acid, such as concentrated sulfuric acid, trifluoromethanesulfonic acid, benzenesulfonic acid, trifluoromethanesulfonic acid, etc., is added to the organic phase to break the Si-O bond between the M unit and the Q unit in the pentamer, and Si-OH is formed at the end of the Q unit. The Q units will continue to undergo polycondensation reactions, and the molecular weight continues to grow, so that the proportion of pentamers is effectively reduced. Since the MQ resin with a larger molecular weight has a lower polycondensation activity than the pentamer, and since the temperature control of the reaction is relatively low, its polycondensation probability is very low, so the polycondensation reaction that occurs mainly between the pentamers in this process greatly reduces the content of the pentamer in the treated MQ resin.

[0029] Preferably, in step S4, the distillation method is continuous distillation or intermittent distillation;

[0030] Preferably, in step S4, the pentamer content in the obtained MQ resin is less than 0.5% of the total weight of the MQ resin.

[0031] Preferably, the weight average molecular weight of the MQ resin is 5,000 to 20,000, more preferably 10,000 to 20,000.

[0032] Compared with the prior art, the beneficial effects of the present invention are:

[0033] In the preparation process of MQ resin, strong acid is used to carry out low-temperature secondary treatment of the crude product, which effectively reduces the content of pentamer in MQ resin, improves the application performance of MQ resin, enhances its initial adhesion in pressure-sensitive adhesive applications and the viscosity-increasing effect when used with low-viscosity adhesives, and can effectively reduce the amount of MQ resin added in the formula. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The structure of the pentamer (tetrakis(trimethylsiloxy)silane) is shown;

[0035] Figure 2 is the GPC chromatogram of MQ resin A prepared according to Example 1;

[0036] Figure 3 is the GPC chromatogram of MQ resin B prepared according to Example 2;

[0037] Figure 4 is the GPC chromatogram of MQ resin C prepared according to Example 3;

[0038] Figure 5 is the GPC chromatogram of MQ resin D prepared according to Example 4;

[0039] Figure 6It is the GPC chromatogram of MQ resin E prepared according to Comparative Example 1. DETAILED DESCRIPTION

[0040] The following examples are used to further illustrate the continuous preparation method of MQ resin with low pentamer content of the present invention. The examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following examples. The experimental methods in the following examples, unless otherwise specified, are conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are purchased from conventional biochemical reagent stores.

[0041] In the examples, the main raw material information used is as follows:

[0042] Raw material name factory purity Water Glass Laizhou Sodium Phosphate 35% hydrochloric acid Far East Fine Chemicals Co., Ltd. 36% Hexamethyldisiloxane Dongyue Chemical Co., Ltd. 99% Trimethylchlorosilane Dongyue Chemical Co., Ltd. 99% Isopropyl alcohol / ethanol Sinopec 99% Xylene / Toluene Sinopec 99% Concentrated sulfuric acid Aladdin 98% Trifluoromethanesulfonic acid Aladdin 99% Benzenesulfonic acid Anaiji 98% Trimethylolsulfonic acid Inokay 99%

[0043] In the examples, the molecular weight and the content of pentamers were quantified by GPC.

[0044] Gel chromatography (GPC): Gel chromatography: equipped with unit pump, column oven, differential detector, autosampler and chromatography workstation. Chromatographic conditions: chromatographic column Agilent PLgel MIXED-D 5um (7.5×300mm) PLgel MIXED-E3um (7.5x300mm), flow rate: 1.0mL / min, column temperature: 40℃, detector temperature: 40℃, injection volume: 10uLs.

[0045] Example 1

[0046] A 20wt% sodium silicate aqueous solution (modulus 3.1) and an 11% hydrochloric acid aqueous solution were continuously injected into a tubular reactor at a speed of 500g / min and 250g / min, respectively. A strong mixing device was provided in the reactor to ensure the mixing effect of the two materials. The pH of the polycondensation reaction was measured to be 0.60. After the two materials were evenly mixed, they were injected into another tubular reactor for aging. The aging time was 2min. The product in the tubular reactor, isopropanol, hexamethyldisiloxane, and trimethylchlorosilane were continuously added to the end-capping reactor at a speed of 750g / min, 150g / min, 350g / min, and 140g / min, respectively. The end-capping reaction temperature was 80°C, and the end-capping reaction time was 3 hours. The product in the end-capping reactor was sent to a continuous phase separator, and the phase separator residence time was 1 hour. Finally, the organic phase separated by the phase separator is continuously injected into the secondary treatment reactor, and benzenesulfonic acid is added to the organic phase at a rate of 1 g / min under stirring, and the treatment temperature is maintained at 25°C for 1 hour. The treated organic phase is continuously washed with deionized water and phase separated. Three-stage water washing is performed continuously, and the upper organic phase after washing enters a continuous distillation tower. The distillation operating temperature is 150°C and the operating pressure is normal pressure. Water and part of the solvent in the product are removed to obtain an MQ resin solution with a solid content of 70%. The obtained product, MQ resin A, was measured by GPC, and the weight average molecular weight was 13082, the molecular weight distribution was 1.39, and the pentamer content was 0.27% (as attached Figure 2 shown).

[0047] Example 2

[0048] A 16wt% sodium silicate aqueous solution (modulus 3.1) and an 8% hydrochloric acid aqueous solution were continuously injected into the autoclave reactor at a speed of 500g / min and 250g / min, respectively. The reactor was vigorously stirred to ensure the mixing effect. The pH of the polycondensation reaction was measured to be 0.72. After the two materials were evenly mixed, they were aged in the autoclave for 10 minutes. The aged product, methanol, xylene, and hexamethyldisiloxane were continuously added to the end-capping reactor at a speed of 750g / min, 120g / min, 350g / min, and 120g / min, respectively. The end-capping reaction temperature was 60°C and the end-capping reaction time was 3 hours. The product in the end-capping reactor was sent to a continuous phase separator, and the phase separator residence time was 1 hour. Finally, the organic phase separated by the phase separator was continuously injected into the secondary treatment reactor, and concentrated sulfuric acid was added to the organic phase at a speed of 0.5g / min under stirring, and the treatment temperature was maintained at 40°C for 1 hour. The treated organic phase was continuously washed with deionized water and separated into phases. Three-stage water washing was performed continuously. After washing, the upper organic phase was intermittently distilled. The maximum operating temperature of the distillation was 150°C and the operating pressure was normal pressure. Water and part of the solvent in the product were removed to obtain an MQ resin solution with a solid content of 70%. The obtained product MQ resin B was measured by GPC. The weight average molecular weight was 12803, the molecular weight distribution was 1.37, and the pentamer content was 0.23% (as shown in the attached Figure 3 shown).

[0049] Example 3

[0050] A 25wt% sodium silicate aqueous solution (modulus 3.1) and a 13% hydrochloric acid aqueous solution were continuously injected into a tubular reactor at a speed of 500g / min and 300g / min, respectively. A strong mixing device was provided in the reactor to ensure the mixing effect of the two materials. The pH of the polycondensation reaction was measured to be 0.55. After the two materials were evenly mixed, they were injected into another tubular reactor for aging. The aging time was 1min. The product, ethanol, toluene, and tetramethyldivinyldisiloxane in the tubular reactor were continuously added to the end-capping reactor at a speed of 850g / min, 170g / min, 380g / min, and 200g / min, respectively. The end-capping reaction temperature was 90°C, and the end-capping reaction time was 3 hours. The product in the end-capping reactor was sent to a continuous phase separator, and the phase separator residence time was 1 hour. Finally, the organic phase separated by the phase separator is continuously injected into the secondary treatment reactor, and trifluoromethanesulfonic acid is added to the organic phase at a speed of 2.5g / min under stirring, and the treatment temperature is maintained at 20°C for 1 hour. The treated organic phase is continuously washed with deionized water and phase-splitting is performed. Three-stage washing is performed continuously, and the upper organic phase after washing enters a continuous distillation tower with a distillation operating temperature of 150°C and an operating pressure of normal pressure. Water and part of the solvent in the product are removed to obtain an MQ resin solution with a solid content of 70%. The resulting product, MQ resin C, was measured by GPC, and the weight-average molecular weight was 13225, the molecular weight distribution was 1.41, and the pentamer content was 0.22% (as attached Figure 4 shown).

[0051] Example 4

[0052] A 20wt% sodium silicate aqueous solution (modulus 3.1) and an 11% hydrochloric acid aqueous solution were continuously injected into a tubular reactor at a speed of 500g / min and 250g / min, respectively. A strong mixing device was provided in the reactor to ensure the mixing effect of the two materials. The pH of the polycondensation reaction was measured to be 0.63. After the two materials were evenly mixed, they were injected into another tubular reactor for aging. The aging time was 2min. The product in the tubular reactor, butanol, n-heptane, and dimethylvinyl chlorosilane were continuously added to the end-capping reactor at a speed of 750g / min, 180g / min, 350g / min, and 160g / min, respectively. The end-capping reaction temperature was 80°C, and the end-capping reaction time was 3 hours. The product in the end-capping reactor was sent to a continuous phase separator, and the phase separator residence time was 1 hour. Finally, the organic phase separated by the phase separator is continuously injected into the secondary treatment reactor, and trimethylsulfonic acid is added to the organic phase at a rate of 1 g / min under stirring, and the treatment temperature is maintained at 30°C for 1 hour. The treated organic phase is continuously washed with deionized water and phase-separated. Three-stage water washing is performed continuously, and the upper organic phase after washing enters a continuous distillation tower with a distillation operating temperature of 150°C and an operating pressure of normal pressure. Water and part of the solvent in the product are removed to obtain an MQ resin solution with a solid content of 70%. The resulting product, MQ resin D, was measured by GPC, and the weight-average molecular weight was 12922, the molecular weight distribution was 1.40, and the pentamer content was 0.35% (as attached Figure 5 shown).

[0053] Comparative Example 1

[0054] A 20wt% sodium silicate aqueous solution (modulus 3.1) and an 11% hydrochloric acid aqueous solution were continuously injected into the tubular reactor at a speed of 500g / min and 250g / min, respectively. A strong mixing device was provided in the reactor to ensure the mixing effect of the two materials. The pH of the polycondensation reaction was measured to be 0.60. After the two materials were evenly mixed, they were injected into another tubular reactor for aging, and the aging time was 2min. The product, isopropanol, hexamethyldisiloxane, and trimethylchlorosilane in the tubular reactor were continuously added to the end-capping reactor at a speed of 750g / min, 150g / min, 350g / min, and 140g / min, respectively. The end-capping reaction temperature was 80°C, and the end-capping reaction time was 3 hours. The product of the end-capping reactor was sent to a continuous phase separator, and the phase separator residence time was 1 hour. The organic phase after phase separation was continuously washed with deionized water, and phase separated again. The three-stage water washing was carried out continuously. After the water washing, the upper organic phase entered a continuous distillation tower. The distillation operation temperature was 150°C and the operation pressure was normal pressure. The water and part of the solvent in the product were removed to obtain an MQ resin solution with a solid content of 70%. The obtained product MQ resin E was measured by GPC. The weight average molecular weight was 12263, the molecular weight distribution was 1.39, and the pentamer content was 1.39% (as shown in the attached Figure 6 shown).

Claims

1. A method for preparing a MQ resin with a low pentamer content, the method comprising the following steps: S1: adding water glass and hydrochloric acid into a polycondensation reactor, mixing them thoroughly, and then aging to obtain a Q prepolymer; S2: adding a capping agent, an alcohol reagent and a solvent to the Q prepolymer to perform a capping reaction; S3: static phase separation to obtain an organic phase containing MQ resin, adding a strong acid to the organic phase, and mixing at a temperature below 50° C., wherein the strong acid is one or more selected from concentrated sulfuric acid, trifluoromethanesulfonic acid, benzenesulfonic acid, and trimethylsulfonic acid; S4: washing with water to remove the strong acid in the organic phase obtained in step S3, and performing distillation separation to obtain MQ resin with low pentamer content.

2. The method for preparing a MQ resin with a low pentamer content according to claim 1, wherein: In step S3, the amount of the strong acid is 0.1-0.5 wt % based on the weight of the added water glass.

3. The method for preparing a MQ resin with a low pentamer content according to claim 1, wherein: In step S3, mixing is performed at a temperature of 20 to 40°C.

4. The method for preparing a MQ resin with a low pentamer content according to claim 1, wherein: The preparation method is carried out in a continuous process, and the polycondensation reactor is a tubular reactor or a kettle reactor.

5. The method for preparing a MQ resin with a low pentamer content according to any one of claims 1 to 4, wherein: In step S1, The water glass concentration is 16-25wt%; and / or The amount of hydrochloric acid added is such that the pH of the reaction system is less than 1; and / or The aging time is 1 to 10 minutes.

6. The method for preparing a MQ resin with a low pentamer content according to claim 5, wherein: In step S1, the concentration of water glass is 20wt%.

7. The method for preparing a MQ resin with a low pentamer content according to any one of claims 1 to 4, wherein: In step S2, The end-capping agent is one or more selected from trimethylchlorosilane, hexamethyldisiloxane, tetramethyldivinyldisiloxane, and dimethylvinylchlorosilane; and / or The amount of the end-capping agent added is 20-40 wt %, based on the weight of the added water glass; and / or The alcohol reagent is one or more selected from methanol, ethanol, isopropanol and butanol; and / or The added amount of the alcohol is 20-40 wt % based on the weight of the added water glass.

8. The method for preparing a MQ resin with a low pentamer content according to claim 7, wherein: The alcohol reagent is isopropanol.

9. The method for preparing a MQ resin with a low pentamer content according to any one of claims 1 to 4, wherein: In step S2, The solvent is one or more selected from toluene, xylene, hexamethyldisiloxane and long-chain hydrocarbon reagents; and / or The amount of the solvent added is 30 to 100 wt % based on the weight of the added water glass; and / or The reaction temperature of the end-capping reaction is 60-90°C.

10. The method for preparing a MQ resin with a low pentamer content according to any one of claims 1 to 4, wherein: In step S4, The distillation method is continuous distillation or intermittent distillation; and / or The pentamer content in the obtained MQ resin is less than 0.5% by weight of the total weight of the MQ resin.

11. The method for preparing a MQ resin with a low pentamer content according to any one of claims 1 to 4, wherein: In step S4, The weight average molecular weight of the obtained MQ resin is 5,000 to 20,000.

12. The method for preparing a MQ resin with a low pentamer content according to claim 11, wherein: The weight average molecular weight of the obtained MQ resin is 10,000 to 20,000.

Citation Information

Patent Citations

  • Preparation method of methyl MQ resin

    CN109438709A

  • Methyl MQ resin and preparation method thereof

    CN109553773A

  • Modified MQ (mono-quad) resin, synthesis method and application on pressure sensitive adhesive

    CN110760068A

  • Method For Capping Mq-Type Silicone Resins

    US20160326320A1